2012
DOI: 10.1523/jneurosci.6033-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit/Hyperactivity Disorder-Derived Coding Variation in the Dopamine Transporter Disrupts Microdomain Targeting and Trafficking Regulation

Abstract: Attention-Deficit Hyperactivity Disorder (ADHD) is the most commonly diagnosed disorder of school-age children. Although genetic and brain imaging studies suggest a contribution of altered dopamine (DA) signaling in ADHD, evidence of signaling perturbations contributing to risk is largely circumstantial. The presynaptic, cocaine and amphetamine (AMPH)-sensitive DA transporter (DAT) constrains DA availability at pre- and post-synaptic receptors following vesicular release and is targeted by the most commonly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(143 citation statements)
references
References 66 publications
5
138
0
Order By: Relevance
“…We recently identified a mutant dopamine transporter (DAT) derived from a subject with Attention Deficit/Hyperactivity Disorder (ADHD) that exhibits an altered ability to adopt normal protein associations and trafficking itineraries. 56 These findings raise the possibility that alterations mimicking the changes observed with the CHT LV- AA mutation may contribute to disorders linked to compromised cholinergic signaling. Since PMA reduces choline transport capacity in parallel with enhanced transporter endocytosis with either WT CHT or CHT LV-AA cells, it seems likely that the sequences that mediate PKCdependent transporter down-regulation lie distal to the LV dileucine motif.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…We recently identified a mutant dopamine transporter (DAT) derived from a subject with Attention Deficit/Hyperactivity Disorder (ADHD) that exhibits an altered ability to adopt normal protein associations and trafficking itineraries. 56 These findings raise the possibility that alterations mimicking the changes observed with the CHT LV- AA mutation may contribute to disorders linked to compromised cholinergic signaling. Since PMA reduces choline transport capacity in parallel with enhanced transporter endocytosis with either WT CHT or CHT LV-AA cells, it seems likely that the sequences that mediate PKCdependent transporter down-regulation lie distal to the LV dileucine motif.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Often, such variation is confined to a single, and sometimes small, pedigree, compelling the demonstration of functional perturbations in vitro and in vivo to make conclusions as to possible disease associations. Our efforts to date have uncovered multiple rare SLC6A3 coding variants in screens of ADHD subjects, with two of these, A559V and R615C, demonstrating altered function after heterologous expression (58,77). Here, we present the first opportunity, to our knowledge, to explore the impact of diseaseassociated, rare DAT variation in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…The peptides had no effect on DA uptake and DAT surface levels, according to uptake and surface biotinylation experiments, respectively, consistent with no effect of the peptides on transporter turnover rate and transporter trafficking. A recent study analyzed the effect of a corresponding DAT peptide, and this peptide also showed no effect on DA uptake in the WT transporter (38).…”
Section: Discussionmentioning
confidence: 99%